Oxidation of manganese in an ancient aquifer, Kimberley formation, Gale crater, Mars. Issue 14 (18th July 2016) - Lanza, Nina L.; Wiens, Roger C.; Arvidson, Raymond E.; Clark, Benton C.; Fischer, Woodward W.; Gellert, Ralf; Grotzinger, John P.; Hurowitz, Joel A.; McLennan, Scott M.; Morris, Richard V.; Rice, Melissa S.; Bell, James F.; et al.
Abstract: The Curiosity rover observed high Mn abundances (>25 wt % MnO) in fracture‐filling materials that crosscut sandstones in the Kimberley region of Gale crater, Mars. The correlation between Mn and trace metal abundances plus the lack of correlation between Mn and elements such as S, Cl, and C, reveals that these deposits are Mn oxides rather than evaporites or other salts. On Earth, environments that concentrate Mn and deposit Mn minerals require water and highly oxidizing conditions; hence, these findings suggest that similar processes occurred on Mars. Based on the strong association between Mn‐oxide deposition and evolving atmospheric dioxygen levels on Earth, the presence of these Mn phases on Mars suggests that there was more abundant molecular oxygen within the atmosphere and some groundwaters of ancient Mars than in the present day. Key Points: Mn‐rich fracture fills discovered on Mars Chemistry and context indicate Mn oxides Past Mars may have had molecular oxygen